Analysis of Reading Skills of Grade 1 Students of SDN 6 Yangapi Through Pop Up Book Media: Analisis Keterampilan Membaca Siswa Kelas 1 SDN 6 Yangapi Melalui Media Pop Up Book - Janawati , Desak Putu Anom; Andika, I Putu Bayu; Pradnyana, Puti Beny (Pedagogia : Jurnal Pendidikan, 2024)
The aim of the research is to analyze children's reading skills through Pop Up Books. Data was collected using a quantitative descriptive method, which means a type of research that uses quantitative data to describe or explain phenomena or variables that can be measured and calculated. The sample was 34 students, namely 17 men and 17 women. The low reading skills in this class are the reason for researchers to research. Reading skills are classified as good (B) with a calculation result of 75%.